2018
DOI: 10.1177/1591019917751894
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the target: Angiographic features of the fistulous point and prognosis of transvenous embolization of cavernous sinus dural arteriovenous fistula

Abstract: Background and purpose Transvenous embolization (TVE) is widely utilized as an effective and safe treatment option for cavernous sinus dural arteriovenous fistula (CS-dAVF); however, detecting the exact location of the fistula is challenging. The present study identified the angiographic features of the fistulous point and evaluated the match with the microcatheter tip and fistulous point. Materials and methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The SP is mainly situated at the posterior compartment of the CS and connects with the intercavernous sinus. It might have one or more of the following angiographic findings: a) an early opacified area in the early arterial phase of catheter angiography, b) a jellyfish-like sign denoting the branches of arterial supply converging at the fistula point, c) changes in the density of the contrast medium from dark in the artery to gray in the veins on the fistula point, d) enlarged and tortuous arterial feeders that can directly point to the fistula point [24,25].…”
Section: Fistula Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…The SP is mainly situated at the posterior compartment of the CS and connects with the intercavernous sinus. It might have one or more of the following angiographic findings: a) an early opacified area in the early arterial phase of catheter angiography, b) a jellyfish-like sign denoting the branches of arterial supply converging at the fistula point, c) changes in the density of the contrast medium from dark in the artery to gray in the veins on the fistula point, d) enlarged and tortuous arterial feeders that can directly point to the fistula point [24,25].…”
Section: Fistula Pointmentioning
confidence: 99%
“…Nevertheless, TVE has become the mainstream EVT for CS-DAVFs, of which the transfemoral IPS approach is the favorite, shortest, and most direct route to the CS [1,15]. In TVE, precise identification of the SP location is crucial because targeted dense embolization of the SP can reduce the amounts of embolic agents used and thus avoid complications [24,25,45].…”
Section: Outline Of Evtmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve complete occlusion of CS DAVFs, the CS needs to be densely packed with coils. Nishino et al [7] found that paradoxical worsening (the devel-opment of new or worsening symptoms or signs after embolization) occurred in 39.4% of patients after transvenous coil embolization, which was correlated with the volume of coils in the CS [8]. Paradoxical worsening may be attributed to progressive thrombosis of the CS, mass effects from the embolic materials, or direct injury to the nerve by the coils or the microwire/microcatheter [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…The primary occlusion rates of 54 to 81% for transarterial and transvenous embolization are heterogeneous but seem to favor the transvenous approach. [26][27][28] A smaller retrospective analysis of occlusion rates of primary stent graft placement reports an occlusion rate of 83%, 23 but prospective comparisons of the different techniques are lacking. Review of current literature shows that up until recent times, multimodal and sometimes sequential approaches are still needed to treat some cases of CCFs.…”
Section: Embolization Techniques Of Carotid Cavernous Fistulasmentioning
confidence: 99%